Targeting adipokines: A new strategy for the treatment of myocardial fibrosis - Xiaoying Han; Yi Zhang; Xinyu Zhang; Haixia Ji; Wenzhe Wang; Ou Qiao; Xia Li; Juan Wang; Changxiao Liu; Luqi Huang; Wenyuan Gao (Elsevier, 2022)
Cardiac fibrosis is a pathogenic factor of many cardiovascular diseases (CVD), which seriously affects people's life and health, causing huge economic losses.Therefore, it is very significant to find an effective treatment for myocardial fibrosis. Adipokines are mainly derived from adipose tissue and have an prominent regulatory effect on glucose and lipid metabolism, inflammation, immune response and cardiovascular function. Adipose tissue is composed of a variety of cell types, including adipocytes, endothelial cells, macrophages and smooth muscle cells. Adipokines mainly include adiponectin, leptin, resistin, visfatin and omentin, which are synthesized and secreted by adipocytes. More and more evidence shows that adipokines can regulate the progress of cardiac fibrosis. This scientific review provides new ideas for targeting adipokines in the treatment of myocardial fibrosis and provides strategies for the development of new, safe, and effective pharmacological antagonists against myocardial fibrosis based on adipokines activity.